MicroRNA let-7d targets thrombospondin-1 and inhibits the activation of human pancreatic stellate cells - Asama, Hiroyuki; Suzuki, Rei; Hikichi, Takuto; Takagi, Tadayuki; Masamune, Atsushi; Ohira, Hiromasa (Pancreatology : official journal of the International Association of Pancreatology (IAP) ... [et al.], 2019)
The microRNA (miRNA) let-7d is linked to the formation of pancreatic cancer-related fibrosis. In this study, the mechanism by which let-7d regulates the activation of the human pancreatic stellate cell (hPSC) was evaluated. The transient transfection of a let-7d mimic in the hPSCs was performed, and the altered thrombospondin 1 (THBS1) expression was confirmed by western blotting and real-time qPCR. Targeting of the 3′-untranslated region (UTR) of THBS1 by let-7d was investigated by the luciferase assays. After hPSC transfection using THBS1 siRNA, the fibrosis markers (α-SMA and collagen 1A1) were evaluated by western blotting and real-time qPCR. The correlation between tumor fibrosis and let-7d or THBS1 was estimated using the data from The Cancer Genome Atlas project. Finally, the effects of genistein on the hPSCs were evaluated. We found that a let-7d mimic inhibits THBS1 expression by targeting its 3′-UTR. THBS1 inhibition by siRNA inhibited hPSC activation. An in silico analysis revealed that let-7d and THBS1 expression are negatively correlated. Additionally, let-7d was negatively correlated with the stromal score, while THBS1 was positively correlated with this score. Genistein substantially induced let-7d and decreased the expression of fibrosis marker along with the inhibition of THBS1. Let-7d inhibited hPSC activation by targeting THBS1. Genistein induced the expression of let-7d and might modulate pancreatic fibrosis.